An expamle of using dimethyl carbonate as an environmetnally begin methylating reagent - Binh, Phan Thanh; Thuc, Le Ngoc; Thu Trang, Nguyen Thi; Tu, Nguyen Viet; Ngat, Nguyen Thi (Vietnam Journal of Chemistry, 2012)
DMC (dimethyl carbonate) was examined as a methylating reagent in the reaction with eugenol affording methyl eugenol – a pesticide used in protecting oranges from the attack of the fruit-flies. The methylated product was obtained in high yield and selectivity. The result showed a possibility to replace the toxic, environmentally harmful methylating reagents such as methyl halides (MeX; X=I, Br, Cl) and dimethyl sulfate (DMS) in the production of methyl eugenol.